Du Sublime de la montagne chez Philip James de Loutherbourg et Joseph Mallord William Turner - Aurélie Tremblet (Revue de Géographie Alpine)
Our analysis of the concept of saliency relies on two iconographic representations of Alpine relief. One is from Philip James de Loutherbourg (An Avalanche in the Alps, 1803); the other from Joseph Mallord William Turner (The Fall of an Avalanche in the Grisons, 1810). This comparative study comes with an analysis of the discourse on saliency as Turner had joined a poem to his pictorial work of art. We will thus study the way both artists have looked upon the Alps: as individuals unfamiliar with mountain relief, and depicting a similar natural disaster —an avalanche—, did they merely focus on the inaccessible and dangerous nature of such places?If there are striking analogies between the two canvases, disclosing the existence of several forms and factors of saliency, common to both artists —and directly echoing the aesthetic notion of the Sublime, which emerged in Great-Britain in the 19th century— these visual manifestations of saliency seem to have equivalents in the linguistic field. We thus follow Frédéric Landragin when trying to demonstrate that the poem as well as the paintings by De Loutherbourg and Turner hinge upon the same two main mechanisms, based on disruption.